Ready for Nuclear Energy?: A Policy Review of the Philippines’ Nuclear Energy Plan and Participation in the ASEAN Network of Regulatory Bodies on Atomic Energy - Julius Cesar Trajano (International Journal of Nuclear Security, 2022)
Recently, the Philippines has been demonstrating its interest in using nuclear energy, including addressing issues and gaps in its nuclear energy preparations, several of which fall under nuclear security, nuclear emergency preparedness and response, and regulatory capacity. This article argues that the ASEAN member states’ growing regional cooperation in nuclear safety and security, spearheaded by the ASEAN Network of Regulatory Bodies on Atomic Energy (ASEANTOM), can have a strong positive impact on the Philippines’ nuclear energy preparations. ASEANTOM’s regional activities and projects can help the Philippines address some of the current critical gaps and issues in its nuclear energy preparatory plans. But there are still limitations to how much regional cooperation can impact the Philippines’ nuclear power preparations. This article is not only just about the Philippines and its plan to use nuclear energy, but also about ASEAN cooperation in nuclear safety, security, and emergency preparedness and response.
Keywords: Nuclear energy; Nuclear security; Philippines; ASEANTOM; ASEAN; regional cooperation